2007
DOI: 10.1002/adsc.200600362
|View full text |Cite
|
Sign up to set email alerts
|

Improved Synthesis of Pyrroles and IndolesviaLewis Acid‐Catalyzed Mukaiyama–Michael‐Type Addition/Heterocyclization of Enolsilyl Derivatives on 1,2‐Diaza‐1,3‐Butadienes. Role of the Catalyst in the Reaction Mechanism

Abstract: Abstract:The Mukaiyama-Michael-type addition of various silyl ketene acetals or silyl enol ethers on some 1,2-diaza-1,3-butadienes proceeds at room temperature in the presence of catalytic amounts of Lewis acid affording by heterocyclization 1-aminopyrrol-2-ones and 1-aminopyrroles, respectively. 1-Aminoindoles have been also obtained by the same addition of 2-(trimethylsilyloxy)-1,3-cyclohexadiene on some 1,2-diaza-1,3-butadienes and subsequent aromatization. Mechanistic investigations indicate the coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 56 publications
(8 reference statements)
3
18
0
Order By: Relevance
“…We have demonstrated that the reactions between 1,2-diaza-1,3-dienes (DDs) and carbonyl compounds [15] or enol silyl derivatives [16] represent useful and convenient entries to 1-aminopyrroles. More recently, we have introduced a new and flexible Knorrrelated strategy for the construction of amply functionalized pyrroles A (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the reactions between 1,2-diaza-1,3-dienes (DDs) and carbonyl compounds [15] or enol silyl derivatives [16] represent useful and convenient entries to 1-aminopyrroles. More recently, we have introduced a new and flexible Knorrrelated strategy for the construction of amply functionalized pyrroles A (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we assume that the regioselective forma- tion of 3a can be explained by ZnCl 2 -catalyzed attack of the terminal carbon atom of 2a at the terminal carbon of the azo-ene system of 1a (Mukaiyama-Michael addition) to give intermediate B. In analogy to our previous studies, [9] the short-lived silylhydrazonic intermediate A is also hypothesized. The addition of TFA subsequently results in the cleavage of the silyl groups to give intermediate C. The latter undergoes an acid-catalyzed cyclization (by attack of the nitrogen atom to the carbonyl group) to give intermediate D. Subsequently, the acid-catalyzed elimination of a water molecule affords the final product 3a (Scheme 1).…”
Section: Resultsmentioning
confidence: 91%
“…In addition, a silylated open-chain intermediate could be successfully isolated and structurally characterized when the reaction was stopped immediately after the disappearance of the starting material (TLC control). [9] In fact, our previous studies suggested that the silyl enol ether rather than the diazadiene is activated by the Lewis acid. Accordingly, we assume that the regioselective forma- tion of 3a can be explained by ZnCl 2 -catalyzed attack of the terminal carbon atom of 2a at the terminal carbon of the azo-ene system of 1a (Mukaiyama-Michael addition) to give intermediate B.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations